Hydrothermal Synthesis and Structural Characterization of BaTiO3 Powder - Mehmood, Muhammad Farhan; Habib, Amir (The Nucleus, 2023)
The main purpose of the present study was to synthesize and characterize the structural morphology of barium titanate (BaTiO3) powder. The synthesis of BaTiO3 powder was carried out by hydrothermal process using barium hydroxide (Ba(OH)2) and titanium dioxide (TiO2) as precursors in a high-pressure stirred reactor autoclave for a 7-hour reaction time at various temperatures (100, 150 and 180 °C). The physical appearance of the synthesized BaTiO3 powder was white crystalline. X-ray diffraction (XRD), Raman spectroscopy, and scanning electron microscopy (SEM) were used to characterize the BaTiO3 powder. Raman spectroscopy and XRD techniques confirm the formation of cubic-phase BaTiO3. Raman peaks at 305 and 516 cm−1 confirmed the formation of BaTiO3. SEM micrographs showed different shapes and a highly dispersed size distribution of particles. The crystal structure of BaTiO3 powder changed as the reaction temperature changed during the synthesis process. The morphological properties of the BaTiO3 powder prepared at 100 °C clearly indicated spherical, irregular, and cubic rod-like structures. The particle size of BaTiO3 powder was very fine at higher reaction temperatures of 150 and 180 °C. Cubic-phase BaTiO3 was obtained in all the synthesized samples. Barium carbonate (BaCO3) and residual unreacted TiO2 phases as impurities were detected in the BaTiO3 powder. The purity of BaTiO3 powder was high at 180 °C under these synthesis conditions.